Disease cycle and infection strategies of systemic plant pathogen Botrytis cinerea - Yahaya, S.M.; Mardiyya, A.Y.; Sakina, S.B.; Hayatu, L.W. (Novel Research in Microbiology Journal)
Botrytis cinerea is a ubiquitous filamentous fungal pathogen of a wide range of plant species. This fungus is able to infect all aerial parts of its host plants; where infection may cause enormous damage both during plant growth and in the post-harvest stage (during cold storage or transport). B. cinerea is a major cause of economic losses in the production chain of cut flowers, bulb flowers and pot plants. Molecular-genetic studies performed over the past decade have provided a wealth of novel insights into the infection mechanisms utilized by this pathogen. Fungal genes important for successful infection by B. cinerea were identified. Such knowledge provided perspectives for designing novel, and rational plant protection strategies that could effectively counteract important pathogen virulence factors. In this study; the infection process will be divided into different stages; moreover, the role of various fungal enzymes and metabolites in the different stages will be discussed. The aim of the current study was to address perspectives for novel control strategies that may reduce and/or delay the damage incited by B. cinerea infection.